Why Do We Get Sick? Some Remarks by Horace on the Causes of Human Ailments - Grzelak-Krzymianowska, Adriana (Collectanea Philologica, 2024)
Quintus Horatius Flaccus, perhaps the most famous Roman poet, vividly portrayed for us in his works both a picture of contemporary society and the world of his thoughts, beliefs and reflections. Among the many well-developed motifs in his work, there are some that have not yet become the subject of in-depth research. These include references of a medical nature. The purpose of this article is to point out places in Horace’s works where he does not so much mention illnesses, but where he gives the causes that make man decline in health. It can therefore be considered that, besides causes beyond human control, the poet’s portrayal of the repertoire of human vices and inappropriate lifestyles is intended to show people that they can improve their existence both physically and spiritually. Horace, by showing the causes of certain diseases and related physical and spiritual afflictions, simultaneously shows man the path to follow in order to be healthy and happy.